Targeting Viperin prevents coxsackievirus B3-induced acute heart failure - Yukang Yuan; Liping Qian; Ying Miao; Qun Cui; Ting Cao; Yong Yu; Tingting Zhang; Qian Zhao; Renxia Zhang; Tengfei Ren; Yibo Zuo; Qian Du; et al. (Cell Discovery)
Abstract Coxsackievirus B3 (CVB3)-induced acute heart failure (AHF) is a common cause of cardiogenic death in young- and middle-aged people. However, the key molecular events linking CVB3 to AHF remain largely unknown, resulting in a lack of targeted therapy strategies thus far. Here, we unexpectedly found that Viperin deficiency does not promote CVB3 infection but protects mice from CVB3-induced AHF. Importantly, cardiac-specific expression of Viperin can induce cardiac dysfunction. Mechanistically, CVB3-encoded 3C protease rescues Viperin protein expression in cardiomyocytes by lowering UBE4A. Viperin in turn interacts with and reduces STAT1 to activate SGK1-KCNQ1 signaling, and eventually leads to cardiac electrical dysfunction and subsequent AHF. Furthermore, we designed an interfering peptide VS-IP1, which blocked Viperin-mediated STAT1 degradation and therefore prevented CVB3-induced AHF. This study established the first signaling link between CVB3 and cardiac electrical dysfunction, and revealed the potential of interfering peptides targeting Viperin for the treatment of CVB3-induced AHF.